Esophageal Blood Flow May Not Be Directly Influenced by Anastomotic Tension: An Exploratory Laser Doppler Study in Swine - Oetzmann von Sochaczewski, Christina; Heimann, Axel; Linder, Andreas; Kempski, Oliver; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2019)
Background Anastomotic tension has been linked to leakage and stenosis in esophageal surgery in both adults and children. We aimed to determine the effects of esophageal topography, operative technique, and anastomotic tension on esophageal blood flow.Materials and Methods We divided and reanastomosed the esophagi at the carinal level with increasing levels of anastomotic tension in piglets (n = 10) and sham controls (n = 4). We examined esophageal blood flow pre- and postoperatively using laser Doppler flowmetry at the anastomosis and two predetermined proximal and distal points. Blood flow in relation to distance from the anastomosis was examined by multivariate linear regression.Results Thoracotomy alone did not influence perfusion at the carinal level in shams (Δ = 3.13 laser Doppler units, 95% confidence interval: −3.4 to 9.7, p = 0.2686). We constructed a (F[5,134] = 6.34, p < 0.0001) multinomial regression model based on distance to the anastomotic site and pre-/postoperative measurements (adjusted R2 = 0.1624). Tissue blood flow was higher distant to the carina, but lower postoperatively and not influenced by the tension resulting from the extent of resection (F[1, 8] = 1.134, p = 0.318).Conclusion Esophageal blood flow is higher at greater distances to the carinal level and hampered by esophageal division and reanastomosis. The extent of resection has less influence than previously assumed. Therefore, leakage and stenosis after esophageal anastomosis may not solely be caused by insufficient anastomotic blood flow.
Keywords: laser Doppler flowmetry; swine model; esophagus; resection; anastomotic tension